2022
DOI: 10.1155/2022/2444516
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Development of Noble Metal NPs for Cancer Therapy

Abstract: With the development of nanotechnology, noble metal nanoparticles are widely used in the treatment of cancer due to their unique optical properties, excellent biocompatibility, surface effects, and small size effects. In recent years, researchers have designed and synthesized a large number of nanomedicines that can be used for cancer treatment based on the morphology, physical and chemical properties, mechanism of action, and toxicological studies of noble metal nanoparticles. Furthermore, the integration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 134 publications
(139 reference statements)
0
35
0
Order By: Relevance
“…Noble metal NPs have attracted a lot of interest in cancer research owing to their unique optical properties and good biocompatibility ( Zhao et al, 2022 ). Combining noble metal-based nanotechnology with diagnostic methods and therapies (from traditional radiotherapy to emerging immunotherapy) has improved the accuracy and efficiency of cancer diagnosis and treatment ( Jiao et al, 2016 ; Mohammadniaei et al, 2019 ; Zhan et al, 2021 ).…”
Section: Biocompatibility and Safety Of Nanomaterialsmentioning
confidence: 99%
See 4 more Smart Citations
“…Noble metal NPs have attracted a lot of interest in cancer research owing to their unique optical properties and good biocompatibility ( Zhao et al, 2022 ). Combining noble metal-based nanotechnology with diagnostic methods and therapies (from traditional radiotherapy to emerging immunotherapy) has improved the accuracy and efficiency of cancer diagnosis and treatment ( Jiao et al, 2016 ; Mohammadniaei et al, 2019 ; Zhan et al, 2021 ).…”
Section: Biocompatibility and Safety Of Nanomaterialsmentioning
confidence: 99%
“…Gold NPs are the most frequently utilized noble metal NPs in tumor diagnosis and treatment due to their unique radiosensitizing properties, good biocompatibility, and relatively low toxicity ( Boisselier and Astruc, 2009 ; Kovács et al, 2022 ; Li et al, 2022 ). Studies have also shown that GNPs may possess certain targeting properties, as demonstrated by the fact that GNPs selectively act on heparin-binding proteins, such as EGFR and VEGFR-2 ( Mukherjee et al, 2005 ; Huang et al, 2021 ; Zhao et al, 2022 ). In addition, it improves the precise delivery and bioavailability of drugs by covalently and non-covalently binding and transporting drug molecules ( Kim et al, 2012 ; Ren et al, 2021 ).…”
Section: Biocompatibility and Safety Of Nanomaterialsmentioning
confidence: 99%
See 3 more Smart Citations